2019
DOI: 10.3390/ijms20174108
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal Nets and Their Role in Synaptic Homeostasis

Abstract: Extracellular matrix (ECM) molecules that are released by neurons and glial cells form perineuronal nets (PNNs) and modulate many neuronal and glial functions. PNNs, whose structure is still not known in detail, surround cell bodies and dendrites, which leaves free space for synapses to come into contact. A reduction in the expression of many neuronal ECM components adversely affects processes that are associated with synaptic plasticity, learning, and memory. At the same time, increased ECM activity, e.g., as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 125 publications
(173 reference statements)
0
58
0
2
Order By: Relevance
“…PNs can regulate and promote functional synaptic plasticity (Bukalo et al, 2001;Balmer et al, 2009;de Vivo et al, 2013;Blosa et al, 2015;Bosiacki et al, 2019). Interestingly, a recent study has shown that PN expression in the medial subdivisions of the auditory thalamus may be responsible for precise neural firing in the aging brain (Quraishe et al, 2019).…”
Section: Potential Functional Roles Of Pns In Age-related Hearing Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…PNs can regulate and promote functional synaptic plasticity (Bukalo et al, 2001;Balmer et al, 2009;de Vivo et al, 2013;Blosa et al, 2015;Bosiacki et al, 2019). Interestingly, a recent study has shown that PN expression in the medial subdivisions of the auditory thalamus may be responsible for precise neural firing in the aging brain (Quraishe et al, 2019).…”
Section: Potential Functional Roles Of Pns In Age-related Hearing Lossmentioning
confidence: 99%
“…PNs can surround a variety of types of neurons throughout the brain although most reports focus on their relationship to GABAergic cells (Kosaka and Heizmann, 1989;Härtig et al, 1992;Sonntag et al, 2015). PNs and their primary molecular component, chondroitin sulfate proteoglycans (CSPGs), are critical for numerous functions including ion buffering, stabilizing high-rate synaptic transmission, modulating cellular integrity, neuroprotection, mechanical stabilization of synaptic contacts, and inhibition of structural plasticity (see reviews Sonntag et al, 2015;Bosiacki et al, 2019;Testa et al, 2019). Of these functions the inhibition of plasticity has garnered the most attention as the enzymatic disruption of PNs can restore juvenile-like plasticity in the adult cortex (Pizzorusso et al, 2002(Pizzorusso et al, , 2006Gogolla et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth remembering that the brain cell activity as well as its effects are influenced by the surrounding environment, which includes a variety of cells, but also the molecules of the ECM, produced by the cells themselves. The complex of these components form the perineural net (PNN) [141]. A reduction in the expression of ECM components can affect synaptic plasticity, but an increase in ECM activity (for example, as a result of pathologic astrogliosis) can also be harmful [141].…”
Section: Evs In the Nervous System: General Considerationsmentioning
confidence: 99%
“…The most well-studied type of ECM is Perineuronal Nets (PNN). This lattice-like structure envelop the soma, stabilizing interneuron activity, regulating synaptic homeostasis (Bosiacki et al, 2019) and protecting interneurons from oxidative damage (Morawski et al, 2004). The role of PNN in mouse model of Aβ amyloidosis have been inconsistent and contradictory.…”
Section: Introductionmentioning
confidence: 99%